Developing familiarity: Rehearsal talk in a newly-formed duo - Bennett, Dawn; Ginsborg, Jane (Oxford University Press, 2021)
How does a newly formed duo of expert musicians negotiate a shared understanding of an unfamiliar work? Two musicians learned two songs over the course of seven days, each musician memorizing one of the songs. A multistrategy approach was used to analyze and triangulate data from their individual practice sessions and joint rehearsals. In this case study, the musicians’ rehearsal talk was analyzed to examine the nature of their socio-emotional interactions, preferred rehearsal strategies, and the features of the music to which they referred. Their interactions were positive: they made suggestions and agreed with each other, provided orientation, relieved tension with humor, and demonstrated solidarity. They tended to repeat short sections, referring most often to tempo, and then ensemble, entries, and dynamics. The study highlights the value of taking an observational approach to the study of collaborative rehearsal and performance, not least for the musicians themselves.